Native Aortic Valve Disease Progression and Bioprosthetic Valve Degeneration in Patients With Transcatheter Aortic Valve Implantation. Issue 17 (29th August 2021) - Kwiecinski, Jacek; Tzolos, Evangelos; Cartlidge, Timothy R.G.; Fletcher, Alexander; Doris, Mhairi K.; Bing, Rong; Tarkin, Jason M.; Seidman, Michael A.; Gulsin, Gaurav S.; Cruden, Nicholas L.; Barton, Anna K.; Uren, Neal G.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Major uncertainties remain regarding disease activity within the retained native aortic valve, and regarding bioprosthetic valve durability, after transcatheter aortic valve implantation (TAVI). We aimed to assess native aortic valve disease activity and bioprosthetic valve durability in patients with TAVI in comparison with subjects with bioprosthetic surgical aortic valve replacement (SAVR). Methods: In a multicenter cross-sectional observational cohort study, patients with TAVI or bioprosthetic SAVR underwent baseline echocardiography, computed tomography angiography, and 18 F-sodium fluoride ( 18 F-NaF) positron emission tomography. Participants (n=47) were imaged once with 18 F-NaF positron emission tomography/computed tomography either at 1 month (n=9, 19%), 2 years (n=22, 47%), or 5 years (16, 34%) after valve implantation. Patients subsequently underwent serial echocardiography to assess for changes in valve hemodynamic performance (change in peak aortic velocity) and evidence of structural valve dysfunction. Comparisons were made with matched patients with bioprosthetic SAVR (n=51) who had undergone the same imaging protocol. Results: In patients with TAVI, native aortic valves demonstrated 18 F-NaF uptake around the outside of the bioprostheses that showed a modest correlation with the time from TAVI ( r =0.36, P =0.023). 18 F-NaF uptake in the bioprosthetic leaflets was comparable between the SAVR and TAVI groups (target-to-background ratio, 1.3 [1.2–1.7] versus 1.3 [1.2–1.5], respectively; P =0.27). The frequencies of imaging evidence of bioprosthetic valve degeneration at baseline were similar on echocardiography (6% versus 8%, respectively; P =0.78), computed tomography (15% versus 14%, respectively; P =0.87), and positron emission tomography (15% versus 29%, respectively; P =0.09). Baseline 18 F-NaF uptake was associated with a subsequent change in peak aortic velocity for both TAVI ( r =0.7, P <0.001) and SAVR ( r =0.7, P <0.001). On multivariable analysis, 18 F-NaF uptake was the only predictor of peak velocity progression ( P <0.001). Conclusions: In patients with TAVI, native aortic valves demonstrate evidence of ongoing active disease. Across imaging modalities, TAVI degeneration is of similar magnitude to bioprosthetic SAVR, suggesting comparable midterm durability. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT02304276.